Temporal Interactions during Paired-Electrode Stimulation in Two Retinal Prosthesis Subjects - Horsager, Alan; Boynton, Geoffrey M.; Greenberg, Robert J.; Fine, Ione (Investigative ophthalmology & visual science, 2011)
Since 2002, six blind patients have undergone implantation of an epiretinal 4 × 4 electrode array designed to directly stimulate the remaining cells of the retina after severe photoreceptor degeneration due to retinitis pigmentosa. This study was conducted to investigate how the brightness of percepts is affected by pulse timing across electrodes in two of these patients. Subjects compared the perceived brightness of a standard stimulus (synchronous pulse trains presented across pairs of electrodes) to the perceived brightness of a test stimulus (pulse trains across the electrode pair phase shifted by 0.075, 0.375, 1.8, or 9 ms). The current amplitude necessary for each phase-shifted test stimulus to match the brightness of the standard was determined. Depending on the electrode pair, interactions between electrodes were either facilitatory (the perceived brightness produced by stimulating the pair of electrodes was greater than that produced by stimulating either electrode alone) or suppressive (the perceived brightness produced by stimulating the pair of electrodes was less than that produced by stimulating either electrode alone). The amount of interaction between electrodes decreased as a function of increased separation both in time (the phase-shift between pulse trains) and space (center-to-center distance between the electrode pair). For visual prostheses to represent visual scenes that are changing in both space and time requires the development of spatiotemporal models describing the effects of stimulation across multiple electrodes. During multielectrode stimulation, interactions between electrodes have a significant influence on subjective brightness that includes both facilitatory and suppressive effects, and these interactions can be described with a simple computational model. (ClinicalTrials.gov number, NCT00279500.).